تأثیر النشر الدولی على ترتیب الجامعات : جامعة القاهرة نموذجا - د. کریمان بکنام صدقى (المجلة الدولية لعلوم المكتبات والمعلومات)
This study aimed to clarify the importance of the international publication as acriterion for the classification of global universities, according to well-known forthe classification of universities in the world standards, and the study provides apresentation of months international rankings of universities, namely,respectively: Classification of Shanghai, rating Thames, rating Aloibometrucs,rating QS; by definition classification and its objectives and standards underlyingrating and highlighting the relative weight of each standard, in addition be clarifiedearly seeded universities globally in each classification in general and to clarifythe order of Cairo University, in particular, whether at the level of internationaluniversities or universities of Arab or Egyptian universities in each classification.